A Mechanical and Histological Comparison of Bone Healing Using Titanium Bone Plates with Porous Surfaced Titanium Screws versus Smooth Surfaced Titanium Screws - Schwarz, P. D.; Bruecker, K. A.; Palmer, J. L.; Powers, Barbara E.; Histand, M. B. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
Bilateral midshaft femoral osteotomies were stabilized with a 3 mm fracture gap in 12 dogs using titanium bone plates and either smooth surfaced (SS) or porous surfaced (PS) titanium screws. Mechanical studies demonstrated that PS screws required a significantly greater torque to remove than the SS screws at both 8 and 16 weeks. At 16 weeks, screw removal torque increased by a factor of 1.3 over the insertion torque for PS screws and decreased by a factor of 2.9 for SS screws. Histologically, the amount of new bone formation and porosity, over the entire length of the femur, was significantly greater in the femora stabilized with PS screws; indicative of greater overall fixation rigidity. At both time periods, there was an increase in torsional stiffness in the osteotomies stabilized with SS screws. Radiographically, there was no difference in the osteotomy callus area for either screw type. From this study, there appears to be advantages to using PS bone screws instead of SS screws when subjected to dynamic loading such as gap fixation.
Keywords: Porous surfaced screws; titanium; gap osteotomy; dynamic loading; bone healing